Laser 3D Printing of Inorganic Free-Form Micro-Optics - Diana Gonzalez-Hernandez; Simonas Varapnickas; Greta Merkininkaitė; Arūnas Čiburys; Darius Gailevičius; Simas Šakirzanovas; Saulius Juodkazis; Mangirdas Malinauskas (Photonics, 2021)
A pilot study on laser 3D printing of inorganic free-form micro-optics is experimentally validated. Ultrafast laser direct-write (LDW) nanolithography is employed for structuring hybrid organic-inorganic material SZ2080TM followed by high-temperature calcination post-processing. The combination allows the production of 3D architectures and the heat-treatment results in converting the material to inorganic substances. The produced miniature optical elements are characterized and their optical performance is demonstrated. Finally, the concept is validated for manufacturing compound optical components such as stacked lenses. This is an opening for new directions and applications of laser-made micro-optics under harsh conditions such as high intensity radiation, temperature, acidic environment, pressure variations, which include open space, astrophotonics, and remote sensing.